Effect of type and content of iron powder on the formation of oxidized film and tribological properties of Cu-matrix composites. (February 2022) - Xu, Wenhu; Fu, Chuanjin; Zhong, Min; Xie, Guoxin; Xie, Xuzhou
Graphical abstract: Highlights: Effects of iron powder types and contents on the friction and wear properties of copper matrix composites for breaking of high-speed trains were investigated through microstructure observations and components analysis of tribofilm. The wettability and combination between ferrophosphorus and matrix is poor and carbonyl iron is more suitable for strengthening matrix. The friction coefficient is most stable and the wear rate is also relatively low with 10% carbonyl iron. The increase of carbonyl iron content can promote the formation of the friction film and improve the thickness, hardness and strength of the film. When the Fe content is larger than 10%, it accelerates the generation of the friction film. However, cracks are easy to form between the thicker film and softening matrix, which leads to large wear and fluctuating friction coefficient. The oxide process during the braking is carried out from the surface to the matrix. The oxide degree of friction film increases in the direction from the matrix to the surface. Abstract: This paper studied the effects of iron powder types and contents on the friction and wear properties of copper matrix composites for breaking of high-speed trains. The mechanical properties, microstructure, interface, tribofilm, elements and microhardness of samples were analyzed by hardness tester, SEM, EDS and nanoindentation tests. The braking performances were measured by a tribometer mimicking the braking conditions. The results show that the wettability and combination between ferrophosphorus and matrix is poor and carbonyl iron is more suitable for strengthening matrix. The friction coefficient is most stable and the wear rate is also relatively low with 10% carbonyl iron. The increase of carbonyl iron content will promote oxidation and be conducive to the formation of friction film. The oxide degree of friction film increases in the direction from the matrix to the surface. However, too much iron powder produces excessive iron oxide which makes the friction film be easy to peel off especially under high speeds.